Development of Hard X-ray Focusing Optics at Diamond Light Source. Issue 4 (3rd July 2016) - Alianelli, Lucia; Laundy, David; Alcock, Simon; Sutter, John; Sawhney, Kawal
Abstract : The short wavelength of X-rays makes them an excellent choice for probing materials on the nanometer scale and for crystallography of sub-micrometer crystallites. The objective of nanofocusing optics is to produce a small, focused beam size in order to obtain the highest X-ray flux on a small sample or as a fine spatial probe. Achieving nanometer-scale focused X-ray beam sizes puts great demands on the optical elements in an X-ray beamline—the optics must balance the requirements to de-magnify the electron beam X-ray source, to reduce the diffraction-limited focus size, and to minimize the contribution to the focus of aberrations in the optics while collecting the maximum X-ray flux into the focused beam. These requirements dictate that an extreme demagnifying geometry should be employed and that high-specification optical elements must be used. Nanofocusing optics has often been added as an upgrade to existing beamlines at Diamond, extending the range of science that can be carried out. Extreme nanofocusing also forms the basis of new beamlines at Diamond, such as the nanoprobe beamline (I14), which aims to provide sub-30-nm-dimension focused X-ray beams for mapping samples at high spatial resolution. The demand for nanometer-scale diffraction-limited X-ray beams is expected to grow at Diamond and requires corresponding advances in X-ray optics to exploit the present source and future lower emittance storage ring sources; for example, the proposed Diamond II upgrade, projected to give a factor 20 emittance reduction.